Zirconia sintered body and manufacturing method of the same

The zirconia sintered body, combining transparent and opaque zirconia with high bending strength, addresses the limitations of conventional ceramic joints by providing strong and aesthetically appealing components suitable for diverse applications.

JP2025016777APending Publication Date: 2025-02-04TOSOH CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2024195875
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-02-18
Filing Date
2024-11-08
Publication Date
2025-02-04

AI Technical Summary

Technical Problem

Conventional ceramic joints, particularly those involving transparent zirconia, suffer from low strength and limited applications due to physical joining methods, making it difficult to create complex shapes and designs.

Method used

A zirconia sintered body composed of transparent and opaque zirconia with a two-axis bending strength of 300 MPa or more, achieved through a sintering process that includes HIP processing, ensuring a strong and aesthetic integration without gaps or third component bonding agents.

Benefits of technology

The zirconia sintered body provides enhanced mechanical strength and design flexibility, allowing for wider applications in components requiring high strength and aesthetic appeal, such as electronic devices and jewelry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025016777000007
    Figure 2025016777000007
  • Figure 2025016777000008
    Figure 2025016777000008
  • Figure 2025016777000009
    Figure 2025016777000009
Patent Text Reader

Abstract

To provide at least one of a zirconia sintered body and a manufacturing method of the zirconia sintered body that can be used in a wider range of applications as compared to the conventional ceramic joined body that contains transparent zirconia.SOLUTION: A zirconia sintered body includes a transparent zirconia portion and an opaque zirconia portion and has a biaxial bending strength of 300 MPa or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a zirconia sintered body and a method for producing the same. [Background technology]

[0002] Ceramics are widely used in industrial materials due to their excellent heat resistance, wear resistance, and corrosion resistance. In particular, the applications of transparent ceramics are expanding due to their high aesthetics and texture. For example, applications of transparent ceramics are being considered for electronic device components such as mobile phones, watch components, and jewelry. With such an expansion of applications, there is a demand for ceramic components that are made of transparent ceramics and ceramics that exhibit different colors, as components that have not only higher aesthetics but also higher designability.

[0003] However, ceramics are a highly tough material and difficult to process into complex shapes, so conventionally, ceramic components with complex shapes have been produced by joining ceramics together.

[0004] For example, a ceramic joined body has been reported in which a colored zirconia sintered body and a transparent zirconia sintered body are joined by shrinking the colored zirconia sintered body to physically fix the transparent zirconia sintered body (Patent Document 1). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2013-14471 A Summary of the Invention [Problem to be solved by the invention]

[0006] The ceramic joint described in Patent Document 1 is a joint produced by utilizing the difference in thermal contraction during heat treatment, and sintered bodies are joined together by physical force. The strength of this joint is low, and the applications for which it can be used are limited.

[0007] An object of the present disclosure is to provide at least one of a zirconia sintered body that can be used in a wider range of applications than conventional ceramic joined bodies containing transparent zirconia and a method for producing the same. [Means for solving the problem]

[0008] In view of the above problems, the present researchers conducted research and found that a specific zirconia sintered body can solve the above problems.

[0009] In other words, the gist of the present disclosure is as follows. [1] A zirconia sintered body having a transparent zirconia portion and an opaque zirconia portion, characterized in that the biaxial bending strength is 300 MPa or more. [2] The zirconia sintered body according to the above [1], in which the transparent zirconia portion and the opaque zirconia portion are on the same plane. [3] The zirconia sintered body according to the above [1] or [2], wherein the transparent zirconia portion has an in-line transmittance of 50% or more. [4] The zirconia sintered body according to any one of [1] to [3] above, wherein the opaque zirconia portion has an in-line transmittance of less than 5%. [5] The zirconia sintered body according to any one of the above [1] to [4], wherein the transparent zirconia portion and the opaque zirconia portion contain zirconia containing a stabilizer and titania. [6] The zirconia sintered body according to the above [5], wherein the stabilizer is at least one selected from the group consisting of yttria, calcia and magnesia. [7] The zirconia sintered body according to the above [5] or [6], wherein the stabilizer for the transparent zirconia portion is yttria, and the yttria content is 6 mol% or more and 12 mol% or less. [8] The zirconia sintered body according to any one of [5] to [7] above, wherein the stabilizer for the opaque zirconia portion is yttria, and the yttria content is 2 mol% or more and less than 6 mol%. [9] The zirconia sintered body according to any one of the above [5] to [8], wherein the opaque zirconia portion has a lower titania content than the transparent zirconia portion.

[10] The zirconia sintered body according to any one of [1] to [9] above, wherein the opaque zirconia portion contains a coloring element.

[11] The zirconia sintered body according to

[10] above, wherein the coloring element is at least one selected from the group consisting of transition metal elements, alkali metal elements, alkaline earth metal elements, aluminum, silicon, boron, phosphorus, germanium, and rare earth elements.

[12] The zirconia sintered body according to any one of [1] to

[11] above, characterized in that the biaxial bending strength is 350 MPa or more.

[13] A method for producing a zirconia sintered body according to any one of the above [1] to

[12] , characterized in that it comprises a sintering step of sintering a secondary molded body formed by stacking a primary molded body made of either a raw material powder of a transparent zirconia part or a raw material powder of an opaque zirconia part and a molded body made of the other raw material powder.

[14] The method for producing a zirconia sintered body according to the above

[13] , wherein the raw material powder of the transparent zirconia part and the raw material powder of the opaque zirconia part are mixed powders containing a stabilizer-containing zirconia source and a titania source, respectively.

[15] The method for producing a zirconia sintered body according to the above

[13] or

[14] , wherein the sintering step includes at least a HIP treatment.

[16] The method according to any one of

[13] to

[15] above, comprising pressureless sintering at 1300°C or higher and 1400°C or lower, followed by HIP treatment at 1450°C or higher and 1550°C or lower. Effect of the Invention

[0010] According to the zirconia sintered body of the present disclosure, it is possible to provide at least one of a zirconia sintered body and a manufacturing method thereof that can be applied to a wider range of applications compared with conventional ceramic joined bodies containing transparent zirconia. [Brief description of the drawings]

[0011] [Figure 1] FIG. 2 is a schematic diagram showing the measurement of biaxial bending strength. [Diagram 2] FIG. 2 is a schematic diagram showing a cross section of a secondary molded body. [Diagram 3] FIG. 2 is a schematic diagram showing the appearance (front and cross section) of the zirconia sintered body of Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, the zirconia sintered body of the present disclosure will be described with reference to an example of an embodiment.

[0013] The present embodiment is a zirconia sintered body having a transparent zirconia portion and an opaque zirconia portion, and characterized in that the biaxial bending strength is 300 MPa or more.

[0014] The zirconia sintered body of this embodiment includes a transparent zirconia part and an opaque zirconia part. This tends to improve aesthetics and design. In another embodiment, the zirconia sintered body of this embodiment is a multi-color zirconia sintered body, that is, a zirconia sintered body having two or more different color tones. In yet another embodiment, the zirconia sintered body of this embodiment is a sintered body including a zirconia sintered body that transmits light and a zirconia sintered body that does not transmit light, and further includes a zirconia sintered body that can be visually recognized as transparent and a zirconia sintered body that can be visually recognized as opaque.

[0015] Yet another embodiment is a zirconia sintered body consisting of a zirconia sintered body made of zirconia having a cubic fluorite structure and a zirconia sintered body made of zirconia having a tetragonal fluorite structure.

[0016] The zirconia sintered body of the present embodiment preferably has a structure in which a transparent zirconia part and an opaque zirconia part are sintered, and more preferably has a structure in which the transparent zirconia part and the opaque zirconia part are sintered in a state in which they form an interface. It is even more preferable that the interface does not have gaps. In addition, "having no gaps" means that an interface between the transparent zirconia part and the opaque zirconia part is formed to such an extent that the strength of the zirconia sintered body of the present embodiment is expressed, and the zirconia sintered body of the present embodiment may have fine defects that do not affect its strength. By having a structure in which the transparent zirconia part and the opaque zirconia are bonded without the intervention of a third component such as a binder, the zirconia sintered body of the present embodiment becomes a sintered body consisting of an integrated sintered structure, and the source of fracture is reduced. In addition, by having a structure in which the transparent zirconia part and the opaque zirconia part are sintered in a state in which they form an interface, the mechanical strength is likely to be higher. Furthermore, since the zirconia sintered body of the present embodiment has a structure in which the transparent zirconia part and the opaque zirconia part are joined without the third component, the zirconia sintered body of the present embodiment includes a grain structure in which the crystal grains of the transparent zirconia part and the crystal grains of the opaque zirconia part are sintered. Therefore, the zirconia sintered body of the present embodiment is different from a zirconia sintered body that does not have the grain structure and a zirconia joined body in which two or more zirconia sintered bodies are simply fitted together. In other words, the zirconia sintered body of the present embodiment is a joined body in which the transparent zirconia part and the opaque zirconia part are joined by sintering, and is different from a joined body in which the transparent zirconia part and the opaque zirconia part are joined only by physical force.

[0017] Generally, a transparent zirconia sintered body has a lower strength than an opaque zirconia sintered body. In contrast, the zirconia sintered body of the present embodiment has a structure in which a transparent zirconia portion is sintered with an opaque zirconia portion, and therefore the strength of the transparent zirconia portion itself tends to be higher than that of the transparent zirconia sintered body alone.

[0018] The shape of the zirconia sintered body of the present embodiment is not particularly limited, but it is preferable that at least the transparent zirconia part and the opaque zirconia part are on the same plane. In the present embodiment, "on the same plane" means on the same plane or the same curved surface, and it is more preferable that the transparent zirconia part and the opaque zirconia part are on the same plane in a visible surface. The structure in which the transparent zirconia part and the opaque zirconia part are arranged on the same plane tends to improve the designability.

[0019] The shape of the zirconia sintered body of this embodiment is arbitrary, and examples thereof include a spherical shape, an approximately spherical shape, a disk shape, a cylindrical shape, an elliptical cylindrical shape, a plate shape, a cube shape, a rectangular parallelepiped shape, a polygonal shape, an approximately polygonal shape, and other shapes according to the application. Furthermore, for example, the shape may include a structure in which either the transparent zirconia part or the opaque zirconia part is arranged so as to surround the other, such as the shape shown in Figure 1 of Patent Document 1, and it is preferable that the opaque zirconia part has a structure surrounding the transparent zirconia part.

[0020] The zirconia sintered body of this embodiment can also be obtained by sintering a molded body in which the precursor of the transparent zirconia part and the precursor of the opaque zirconia part are in contact with each other without any gaps. Therefore, the zirconia sintered body of this embodiment has a high degree of freedom in shape, and can also be obtained as a zirconia sintered body having a complex shape. For example, the zirconia sintered body of this embodiment may include a structure in which either the transparent zirconia part or the opaque zirconia part has an uneven shape, and the other is laminated so that the uneven shapes are combined.

[0021] In the zirconia sintered body of the present embodiment, the ratio of the transparent zirconia part to the opaque zirconia part can be arbitrarily selected depending on the desired aesthetics and shape. For example, the volume ratio of the transparent zirconia part: the opaque zirconia part may be 1:99 to 99:1. do.

[0022] The zirconia sintered body of this embodiment may have a structure in which either the transparent zirconia part or the opaque zirconia part forms a pattern on the surface of the other. Here, the "pattern" refers to a line, figure, or combination thereof formed on either the transparent zirconia part or the opaque zirconia part of the other zirconia part in a visible part of the zirconia sintered body of this embodiment, such as the surface. Examples of the line can be solid lines, dashed lines, wavy lines, and other linear shapes, numbers, letters, and symbols, and examples of the figure can be polygons such as triangles, squares, and pentagons, and geometric shapes such as circles and ellipses. The pattern can be, for example, 1 cm 2 The following areas, even 1mm 2 Areas below or even 0.5 mm 2 The area below or even 0.05 mm 2 The following areas, or even 0.005 mm 2 Examples of the region include those formed in the following areas: Further examples include line drawings consisting of lines with a thickness of about 150 μm, line drawings or figures with intervals of about 150 μm, and figures with a diameter of 1 mm or less, and even figures with a diameter of 0.5 mm or less.

[0023] Since the zirconia sintered body of the present embodiment has particularly excellent aesthetics, it is preferable that the zirconia sintered body of the present embodiment does not have color bleeding. It is considered that color bleeding occurs when a certain amount or more of a coloring element in either the transparent zirconia part or the opaque zirconia part diffuses into the other zirconia part. Here, the "coloring element" refers to an element that produces a coloring effect in zirconia, and its existence state is not limited to ions, oxides, complex oxides, etc. In the present embodiment, "color bleeding" refers to a state in which a coloring element in either the transparent zirconia part or the opaque zirconia part is contained in the other, and is observed visually or with an optical microscope mainly at the interface between the transparent zirconia part and the opaque zirconia part and the region near the interface (hereinafter also referred to as the "transition region").

[0024] In order to obtain a zirconia sintered body having superior aesthetics, it is preferable that the content of the coloring element in the region of the transparent zirconia part within 20 μm from the interface is 0.5 mass % or less, and more preferably 0.3 mass % or less. The content of the coloring element in the transition region can be measured by composition analysis using an EPMA or the like.

[0025] The zirconia sintered body of the present embodiment has a volume ratio (g / cm 2 ) measured by the Archimedes method to a mass measured by mass measurement. 3 ) (hereinafter referred to as "actual density") is 5.8 g / cm 3 More than 6.10g / cm 3 Below that, 5.9g / cm 3 More than 6.0g / cm 3 The following can be exemplified.

[0026] The relative density of the zirconia sintered body of this embodiment is preferably 99.5% or more, more preferably 99.7% or more, and even more preferably 99.9% or more.

[0027] In this embodiment, the relative density of the zirconia sintered body can be calculated from the following formula. Relative density (%) = measured density of zirconia sintered body (g / cm 3 ) / apparent true density of zirconia sintered body (g / cm 3 ) x 100

[0028] The measured density (sintered body density) of the zirconia sintered body is a density determined by Archimedes' method, and the apparent true density of the zirconia sintered body is a density calculated from the apparent true density and volume ratio of each of the transparent zirconia part and the opaque zirconia part according to the following formula. M = (Ma·X+Mb·Y) / (X+Y)

[0029] In the above formula, M is the apparent true density of the zirconia sintered body (g / cm 3 ), Ma is the apparent true density of the transparent zirconia part (g / cm 3 ), Mb is the apparent true density of the opaque zirconia part (g / cm 3), X is the volume ratio of the transparent zirconia portion to the volume of the zirconia sintered body, and Y is the volume ratio of the opaque zirconia portion to the volume of the zirconia sintered body. Ma and Mb are the densities of the HIP-treated bodies of the respective sintered bodies measured by Archimedes' method. The HIP-treated bodies are sintered bodies having a density equivalent to a relative density of 100%, which can be produced by HIP-treating a primary sintered body having a relative density of 97% or more but less than 100% at 150 MPa and 1500°C for 1 hour using argon as a pressure medium.

[0030] The zirconia sintered body of this embodiment has a biaxial bending strength of 300 MPa or more. If the biaxial bending strength is less than 300 MPa, it is easily broken and the applications in which it can be used are limited. Since the zirconia sintered body of this embodiment can be applied to members requiring higher strength, it is preferable that the biaxial bending strength is 350 MPa or more, further 400 MPa or more, further 450 MPa or more, further 500 MPa or more, or further 600 MPa or more. In addition, the biaxial bending strength of this embodiment is 2000 MPa or less, further 1000 MPa or less, further 900 MPa or less, or further 800 MPa or less.

[0031] The biaxial bending strength in this embodiment can be measured by a method conforming to the biaxial bending strength measurement method specified in ISO / DIS6872.

[0032] In the measurement of biaxial bending strength, a plurality of supports are used for placing the measurement sample. The supports are placed so that the interface surrounding the transparent zirconia part or the opaque zirconia part of the measurement sample fits within a circle (support circle) drawn by connecting the supports. The biaxial bending strength may be measured by applying a load having a size smaller than the interface to the center of gravity of the support diameter for the measurement sample placed so that the interface fits within the support circle. For example, when a zirconia sintered body having a shape in which a disc-shaped transparent zirconia part with a diameter of 5 mm is surrounded by an opaque zirconia part is used as the measurement sample, three or more supports (for example, 3 to 5 ceramic balls) may be placed so that the diameter of the support circle is more than 5 mm. In the measurement, a load may be applied to the center of gravity (center) of the support circle using an indenter with a diameter of less than 5 mm.

[0033] FIG. 1 is a schematic diagram showing the measurement of biaxial bending strength, and shows a zirconia sintered body placed on a support. 100a shows a view of the zirconia sintered body when measuring the biaxial bending strength from the bottom (i.e., the surface where the support and the zirconia sintered body contact each other), and 100b shows a cross section of the zirconia sintered body. The supports (110a to 110c) are arranged so that the transparent zirconia part (101) fits inside the support circle. The zirconia sintered body is arranged so that the opaque zirconia part (102) is placed on each support. The biaxial bending strength can be measured by applying a load (120) to the center of gravity of the support circle.

[0034] In this embodiment, the "transparent zirconia part" is made of a clear zirconia sintered body, and is made of a zirconia sintered body having transparency. Furthermore, the transparent zirconia part is preferably made of a zirconia sintered body that can be visually recognized as having transparency, more preferably made of a colorless zirconia sintered body, and even more preferably made of a zirconia sintered body having a high transmittance of incident light, particularly a linear transmittance. The transparent zirconia part preferably has a linear transmittance of 50% or more. If the linear transmittance is 50% or more, it is easily visually recognized as transparent. The linear transmittance is more preferably 60% or more, and even more preferably 70% or more. This provides the transparent zirconia part with aesthetics that are particularly suitable for applications such as watch covers and display members for electronic devices. The linear transmittance of the transparent zirconia part is 75% or less.

[0035] In this embodiment, the "linear transmittance" refers to the linear transmittance when the sample is 1 mm thick and the light source is D65, and is a transmittance having the following relationship: Ti = Tt - Td Tt: Total light transmittance (%) Td: Diffuse transmittance (%) Ti: Linear transmittance (%)

[0036] The D65 light source is one of the standards for light sources that substitute for the standard light source defined by the International Commission on Illumination (Commission internationale l'eclairage; CIE). This light source is light equivalent to natural daylight. Therefore, when the zirconia sintered body of the present embodiment has a sample thickness of 1 mm, it may be confirmed that the zirconia sintered body of the present embodiment has a transparent zirconia portion by confirming that the linear transmittance is 50% or more, further 60% or more, or even 70% or more.

[0037] The transparent zirconia portion is preferably a zirconia sintered body containing zirconia having a cubic fluorite structure, more preferably a zirconia sintered body having zirconia having a cubic fluorite structure as a main phase, and even more preferably a zirconia sintered body made of zirconia having a cubic fluorite structure.

[0038] The zirconia sintered body contained in the transparent zirconia part preferably has an average crystal grain size of 5 μm or more and 200 μm or less. In this embodiment, the average crystal grain size is the average diameter of the zirconia crystal grains of the zirconia sintered body, which can be obtained by the intercept method from an observation diagram obtained by a scanning electron microscope (SEM). The surface of the sintered body is observed at a magnification of 15,000 times, and 200 or more, preferably 250±30, zirconia crystal grains are extracted from the obtained SEM observation diagram, and the crystal grain size is measured by the intercept method (k=1.78), and the average value can be obtained. As the measurement of the average crystal grain size, for example, a scanning electron microscope (device name: JSM-IT100, manufactured by JEOL) is used, and the SEM observation diagram obtained under the following measurement conditions is analyzed by the intercept method using commercially available analysis software (product name: Intouch scope), and the average value of the obtained particle diameters is obtained. Accelerating voltage: 10kV Measurement magnification: 400~10000x

[0039] The transparent zirconia part may have any composition as long as it is a sintered body that exhibits transparency. The transparent zirconia part may be formed by adding a stabilizer and titania (TiO 2 ) containing zirconia.

[0040] As a stabilizer, yttria (Y 2 O 3 At least one selected from the group consisting of yttria (Y), calcia (CaO) and magnesia (MgO) is preferred.

[0041] The content of the stabilizer in the transparent zirconia portion is preferably an amount that stabilizes zirconia in a cubic fluorite structure. For example, when the stabilizer is yttria, the content of yttria is 6 mol% to 12 mol%, preferably 7 mol% to 12 mol%, more preferably 8 mol% to 11 mol%, and even more preferably 8 mol% to 10 mol%.

[0042] In this embodiment, the content of the stabilizer is calculated as the oxide equivalent of the stabilizer and zirconia (ZrO 2 The ratio (mol%) of the stabilizer to the total of zirconia and yttria is calculated by {[stabilizer (mol)] / [zirconia (mol)+stabilizer (mol)]}×100. The oxide equivalent of the stabilizer is Y, 2 O 3 For example, the calcia may be CaO and the magnesia may be MgO. The content of the stabilizer (yttria content) in the zirconia sintered body containing yttria as a stabilizer is {[Y 2 O 3 (mol)] / [ZrO 2 (mol)+Y 2 O 3 (mol)] × 100.

[0043] Since the transparency of the transparent zirconia portion is likely to be high, the titania content of the transparent zirconia portion is 3 mol % or more and 20 mol % or less, preferably 5 mol % or more and 15 mol % or less, and more preferably 8 mol % or more and 12 mol % or less.

[0044] In this embodiment, the content of titania is the ratio of the total of zirconia, the stabilizer calculated as an oxide, and titania (TiO 2 ) (mol%), which is calculated from {[titania (mol)] / [zirconia (mol) + stabilizer (mol) + titania (mol)]} × 100.

[0045] The transparent zirconia part is made of hafnia (HfO 2 In addition to unavoidable impurities such as As long as it does not cause coloring, it may contain coloring elements. For example, the transparent zirconia part may contain aluminum as Al 2 O 3 In terms of the content, the content is 0 mass % or more and 0.1 mass % or less.

[0046] The "opaque zirconia part" is made of a non-transparent zirconia sintered body, and is made of a zirconia sintered body that has no transparency. Furthermore, the opaque zirconia part is preferably made of a zirconia sintered body that can be visually recognized as not having transparency, more preferably made of a colored zirconia sintered body, and even more preferably made of a zirconia sintered body with low transmittance of incident light. Since the visibility of the interface with the transparent zirconia part is increased, the opaque zirconia part is preferably made of an achromatic zirconia sintered body.

[0047] The opaque zirconia portion preferably has a linear transmittance of less than 5%, more preferably less than 4%, even more preferably less than 3%, and even more preferably less than 2%. A zirconia sintered body with a linear transmittance of less than 5% is easily visually recognized as opaque. When all incident light is reflected and / or all transmitted light is diffusely transmitted, the linear transmittance of the zirconia sintered body is 0%. Therefore, the linear transmittance of the opaque zirconia portion is 0% or more. Therefore, the zirconia sintered body of the present embodiment may be confirmed to have an opaque zirconia portion by including a region with a linear transmittance of less than 50%, further less than 10%, further less than 5%, further less than 4%, or further less than 2% when the sample thickness is 1 mm.

[0048] The opaque zirconia portion is preferably a zirconia sintered body containing zirconia having a tetragonal fluorite structure, more preferably a zirconia sintered body having zirconia having a tetragonal fluorite structure as a main phase, and further preferably a zirconia sintered body made of zirconia having a tetragonal fluorite structure.

[0049] The average crystal grain size of zirconia contained in the opaque zirconia portion is preferably 0.1 μm or more and 50 μm or less.

[0050] The opaque zirconia portion may have any composition as long as it is a zirconia sintered body that does not have transparency. A preferred composition of the opaque zirconia portion is zirconia containing a stabilizer and titania, and it is preferable that the opaque zirconia portion contains a coloring element and the remainder is zirconia containing a stabilizer and titania.

[0051] The stabilizer contained in the opaque zirconia portion is at least one selected from the group consisting of yttria, calcia and magnesia, and is preferably yttria.

[0052] The content of the stabilizer is preferably an amount that stabilizes zirconia in a tetragonal fluorite structure. For example, when the stabilizer is yttria, the content of yttria in the opaque zirconia portion is 2 mol% to 6 mol%, preferably 2 mol% to 4 mol%, and more preferably 2.5 mol% to 3.5 mol%.

[0053] Since the mechanical strength tends to be high, the titania content of the opaque zirconia portion is 1 mol % or more and 7 mol % or less, and preferably 1.5 mol % or more and 6 mol % or less.

[0054] In the zirconia sintered body of the present embodiment, the transparent zirconia portion and the opaque zirconia portion preferably contain zirconia containing a stabilizer and titania.

[0055] When the transparent zirconia portion and the opaque zirconia portion each contain titania, the opaque zirconia portion preferably has a lower titania content than the transparent zirconia portion, and further, the difference in titania content between the transparent zirconia portion and the opaque zirconia portion is preferably 2 mol% or more and 10 mol% or less, and more preferably 3 mol% or more and 7 mol% or less.

[0056] The color tone of the opaque zirconia portion is arbitrary, and may be any of white, red, yellow, orange, pink, green, blue, purple, gray, and black. As a color tone with a more profound feeling and high aesthetic appeal, at least one of blue and black may be mentioned, as a general-purpose color tone, any color tone selected from the group of white, gray, and black, and as a color tone rich in decorativeness, any color tone selected from the group of red, yellow, orange, and pink may be mentioned.

[0057] In order to achieve such a color tone, the opaque zirconia portion preferably contains an element (coloring element) that produces a coloring effect on zirconia. Examples of the coloring element contained in the opaque zirconia portion include at least one selected from the group consisting of transition metal elements, alkali metal elements, alkaline earth metal elements, aluminum (Al), silicon (Si), boron (B), phosphorus (P), germanium (Ge), and rare earth elements, and preferably at least one selected from the group consisting of aluminum, nickel (Ni), cobalt (Co), manganese (Mn), iron (Fe), cerium (Ce), praseodymium (Pr), neodymium (Nd), europium (Eu), and erbium (Er), and more preferably at least one selected from the group consisting of aluminum, cobalt, and iron. The sintered body of the present embodiment may, for example, contain any one of at least cobalt and iron, at least cobalt, iron and manganese, at least cobalt, iron and aluminum, or at least cobalt, iron, aluminum and manganese as a coloring element.

[0058] The opaque zirconia part may contain unavoidable impurities such as hafnia, but preferably does not contain zinc (Zn) and chromium (Cr). The zinc and chromium contents are each 0 mass% or more, less than 0.1 mass%, and even 0.05 mass% or less, and are preferably below the detection limit in general composition analysis (for example, 0.005 mass% or less). The total content of zinc and chromium is the content calculated as an oxide, which is the ratio of zinc to zinc oxide (ZnO) and chromium to chromium oxide (CrO) relative to the mass of the opaque zirconia part. 2 O 3) is the percentage of the total mass converted into

[0059] Since the interface between the transparent zirconia part and the opaque zirconia part becomes clearly visible, the opaque zirconia part is * a * b * The color tone of the color system is lightness L * is less than or equal to 10, and Hue a * is between -2.00 and 2.00, and hue b * For example, the preferable color tone and brightness L of the opaque zirconia part is -2.00 or more and 5.00 or less. * is 0 or more and 9.0 or less, preferably 0 or more and 5.5 or less, more preferably 0 or more and less than 3.0, * is -3.00 or more and 2.00 or less, preferably -0.1 or more and 0.80 or less, more preferably -0.50 or more and 0.50 or less, and hue b * is -2.00 or more and 4.00 or less, preferably -1.50 or more and 2.50 or less, and more preferably -1.00 or more and 1.00 or less.

[0060] L * a * b * The color tone of the color system is obtained by measuring a sintered body having a surface roughness (Ra) of 0.02 nm or less by a method conforming to JIS Z 8722. The color tone can be measured using a general color difference meter (e.g., Spectrophotometer SD 3000, manufactured by Nippon Denshoku Industries Co., Ltd.). The color tone is measured using a white plate as the background (so-called white back measurement), and can be measured under the following conditions, for example. Light source: D65 light source Viewing angle: 10° Measurement method: SCE

[0061] The opaque zirconia portion has a monoclinic ratio of preferably 10% or less, more preferably 6.5% or less, further preferably 2% or less, and particularly preferably 1% or less. The monoclinic ratio is a value calculated from the XRD pattern of the surface of the sintered body by the following formula. Monoclinic ratio (%) = [I m (111)+I m (11-1)] × 100 / [I m (111)+I m (11-1)+I t (111)+I c (111)]

[0062] In the above formula, I m (111) is the surface intensity of the (111) plane of monoclinic zirconia, I m (11-1) is the surface intensity of the (11-1) plane of monoclinic zirconia, I t (111) is the surface intensity of the (111) plane of tetragonal zirconia, and I c (111) is the surface intensity of the (111) plane of cubic zirconia. The XRD pattern of the sintered body can be measured, for example, using a general XRD device (for example, device name: RINT-UltimaIII, manufactured by Rigaku Corporation) under the following conditions. Radiation source: CuKα radiation (λ=0.15418nm) Measurement mode: Continuous scan Scan speed: 4° / min Step width: 0.02° Measurement range: 2θ=26°~33°

[0063] Furthermore, the peak intensity of each plane can be determined by analyzing the obtained XRD pattern using commercially available analysis software (for example, RINT-ULTIMA III, manufactured by Rigaku Corporation).

[0064] The average crystal grain size of the zirconia contained in the opaque zirconia portion is preferably 3.0 μm or less, more preferably 2.5 μm or less, and particularly preferably 0.3 μm to 2.5 μm, further preferably 0.5 μm to 1.3 μm.

[0065] The zirconia sintered body suitable for the opaque zirconia part contains a solid solution containing cobalt and iron, the remainder being zirconia, and the cobalt is Co 3O 4 The iron content converted into Fe 2 O 3 In the present invention, a zirconia sintered body having a total content calculated as ZnO / ZnO+ of more than 0.1 mass % and less than 3.0 mass % (hereinafter, also referred to as a "black zirconia sintered body") can be mentioned.

[0066] The black zirconia sintered body is 5.0μm in element mapping by electron beam microanalyzer. 2 It is preferred that the percentage of the area of ​​cobalt exceeding 15% or less, and more preferably that the percentage is 5% or less.

[0067] The black zirconia sintered body preferably contains at least one selected from the group consisting of vanadia and titania, and more preferably contains titania.

[0068] The black zirconia sintered body preferably contains aluminum, and the aluminum content is 0.1 mass% or more and 3.0 mass% or less, preferably 0.1 mass% or more and 2.0 mass% or less, and more preferably 0.1 mass% or more and 1.0 mass% or less. The aluminum content is the ratio of Al to the mass of the black zirconia sintered body. 2 O 3 This is the converted mass percentage of aluminum.

[0069] The black zirconia sintered body may contain manganese, and the manganese content is 0.1 mass% or more and 5.0 mass% or less, preferably 0.2 mass% or more and 3.0 mass% or less, and more preferably 0.3 mass% or more and 2.5 mass% or less. The manganese content is the ratio of Mn 3 O 4 This is the converted mass ratio of manganese.

[0070] The black zirconia sintered body may contain silica, and the silica content is 0.1 mass% or more and 5.0 mass% or less, preferably 0.2 mass% or more and 3.0 mass% or less, and more preferably 0.3 mass% or more and 2.5 mass% or less. The silica content is the ratio of SiO 2 This is the converted mass ratio of silicon.

[0071] For example, when the sintered body contains cobalt, iron, manganese, and aluminum, and the balance is zirconia containing titania and yttria, the aluminum content (mass%) is Al 2 O 3 (g) / {Y 2 O 3 (g) + ZrO 2 (g)+TiO 2 (g)+Fe 2 O 3 (g)+Co 3 O 4 (g)+Mn 3 O 4 (g) + Al 2 O 3 (g)}×100, and the manganese content (mass%) is Mn 3 O 4 (g) / {Y 2 O 3 (g) + ZrO 2 (g)+TiO 2 (g)+Fe 2 O 3 (g)+Co 3 O 4 (g)+Mn 3 O 4 (g) + Al 2 O 3 (g)} × 100.

[0072] The particularly preferred composition of the black zirconia sintered body is Co. 3 O 4 Cobalt, Fe, equivalent to 0.02% or more by mass and 0.2% or less by mass 2 O 3 Iron and Al, calculated as 0.03% or more by mass and 0.5% or less by mass 2 O 3Zirconia containing 0.1 mass % or more and 20 mass % or less of aluminum converted into Co, with the balance being 2 mol % or more and 6 mol % or less of titania and 2 mol % or more and 5 mol % or less of yttria. 3 O 4 Cobalt, Fe, equivalent to 0.02% or more by mass and 0.2% or less by mass 2 O 3 Iron and Al, calculated as 0.03% or more by mass and 0.5% or less by mass 2 O 3 % or more and 2% or less by mass of aluminum, with the remainder being zirconia containing 2 mol % or more and 6 mol % or less of titania and 2 mol % or more and 4 mol % or less of yttria.

[0073] Next, a method for producing the zirconia sintered body of this embodiment will be described.

[0074] The zirconia sintered body of the present embodiment can be produced by a production method including a sintering step of sintering a secondary molded body formed by stacking a primary molded body made of either a raw material powder of a transparent zirconia part or a raw material powder of an opaque zirconia part and a molded body made of the other raw material powder.

[0075] The molded body subjected to the sintering step is a secondary molded body (hereinafter simply referred to as "secondary molded body") which is laminated with a primary molded body (hereinafter simply referred to as "primary molded body") made of either the raw material powder of the transparent zirconia part (hereinafter also referred to as "transparent raw material") or the raw material powder of the opaque zirconia part (hereinafter also referred to as "opaque raw material"), and a molded body made of the other raw material powder.

[0076] The primary molded body is either a molded body made of a transparent raw material (hereinafter also referred to as a "transparent molded body") or a molded body made of an opaque raw material (hereinafter also referred to as an "opaque molded body"). The secondary molded body is a molded body in which the primary molded body and a molded body made of the other raw material powder are stacked, and is a molded body made of a transparent molded body and an opaque molded body. In a preferred embodiment, the secondary molded body is a molded body in which a transparent molded body and an opaque molded body are bonded together. Note that the terms "primary" and "secondary" in the molded body are terms used for convenience to indicate a stacked state, and do not indicate top and bottom or order.

[0077] The shapes of the primary compact and the secondary compact are each arbitrary, and may be the same as the desired sintered body, taking into consideration the shrinkage caused by sintering. Furthermore, in the secondary compact, the primary compact may have at least one of a convex and concave structure, and the compact made of the other raw material powder may have a laminated structure so as to cover the structure.

[0078] The manufacturing method of the primary molded body and the secondary molded body is arbitrary. As a molding method, first, one of the raw material powders of a transparent raw material or an opaque raw material is filled into a mold, then the other raw material powder is layered on the one raw material powder, and then this is molded to obtain a primary molded body and a secondary molded body at the same time. Also, a molding method in which one raw material powder is first filled into a mold and molded to obtain a primary molded body, and then the other raw material powder on it is layered on the primary molded body to mold it into a secondary molded body, and a molding method in which one raw material powder is filled into a mold and molded to obtain a primary molded body, and then the primary molded body is placed in a mold for the secondary molded body, and the other raw material powder is layered on the primary molded body to mold it into a secondary molded body can be exemplified.

[0079] The molding method for the primary molded body and the secondary molded body can be a known molding method, and examples of the molding method include one or more molding methods selected from the group consisting of uniaxial pressure molding, cold isostatic pressing (CIP) treatment, slip casting, sheet molding, and injection molding, and preferably one or more methods selected from the group consisting of uniaxial pressure molding, CIP treatment, and injection molding.

[0080] When the molding method is uniaxial pressure molding, the uniaxial pressure conditions can be exemplified as 20 MPa or more and 70 MPa or less, when the molding method is CIP treatment, the CIP treatment conditions can be exemplified as 150 MPa or more and 250 MPa or less, when the molding method is injection molding, the injection molding conditions can be exemplified as 50 MPa or more and 150 MPa or less, and further 70 MPa or more and 130 MPa or less.

[0081] The transparent raw material is a precursor of the transparent zirconia portion, while the opaque raw material is a precursor of the opaque zirconia portion. The transparent raw material and the opaque raw material are usually powders having different compositions, and these raw material powders may have compositions that become a transparent zirconia sintered body and an opaque zirconia sintered body, respectively, by sintering.

[0082] The transparent raw material and the opaque raw material are preferably mixed powders containing a zirconia source, a stabilizer source, and a titania source, respectively, and more preferably mixed powders containing a stabilizer-containing zirconia source and a titania source, respectively. Furthermore, the transparent raw material and the opaque raw material may contain at least one of coloring element sources.

[0083] The zirconia source is zirconia or a precursor thereof, and is preferably zirconia in a calcined state from a zirconia sol, more preferably zirconia in a calcined state from a zirconia sol obtained by at least one of a hydrothermal synthesis method and a hydrolysis method, and even more preferably zirconia in a calcined state from a zirconia sol obtained by a hydrolysis method.

[0084] The stabilizer source is a stabilizer or a precursor thereof, and may be one or more selected from the group consisting of oxides, chlorides, and hydroxides containing a stabilizing element. When the stabilizer is yttria, the stabilizer source (yttria source) may be one or more selected from the group consisting of yttria, yttrium chloride, and yttrium hydroxide, and is preferably at least one of yttria and yttrium chloride. When the stabilizer is calcia, the stabilizer source (calcia source) may be at least one selected from the group consisting of calcia, calcium chloride, and calcium hydroxide, and is preferably at least one of calcia and calcium chloride. When the stabilizer is magnesia, the stabilizer source (magnesia source) may be at least one selected from the group consisting of magnesia, magnesium chloride, and magnesium hydroxide, and is preferably at least one of magnesia and magnesium chloride.

[0085] The titania source is titania or a precursor thereof, and can be exemplified by one or more selected from the group consisting of titania, titanium chloride, titanium hydroxide, and titanium tetraisopropoxide. At least one of titania and titanium chloride is preferable, and titania is more preferable. More preferable titania sources are those having a purity of 99.9% or more and a BET specific surface area of ​​10 m 2 / g or more 100m 2 The titania powder preferably has a BET specific surface area larger than those of the zirconia source and the stabilizer-containing zirconia source.

[0086] The stabilizer-containing zirconia source is zirconia in which a stabilizer is dissolved, and can be exemplified by one or more selected from the group consisting of yttria-containing zirconia, calcia-containing zirconia, and magnesia-containing zirconia. Yttria-containing zirconia is preferred. A preferred yttria-containing zirconia source is one having a purity of 99.9% or more and a BET specific surface area of ​​5 m 2 / g or more 20m 2 / g or less, an average crystallite size of 10 nm or more and 50 nm or less, and an average secondary particle size of 100 nm or more and 500 nm or less, and further, the yttria-containing zirconia powder is preferably obtained by at least one of a hydrothermal synthesis method and a hydrolysis method.

[0087] The coloring element source is included to give the zirconia portion a desired color. The coloring element source is a compound containing a coloring element, and examples of the coloring element source include at least one selected from the group consisting of oxides, hydroxides, oxyhydroxides, chlorides, sulfides, acetates, nitrates, and sulfates of the coloring element, and preferably at least one selected from the group consisting of oxides, hydroxides, and oxyhydroxides of the coloring element. When the coloring element is cobalt, the coloring element source (cobalt source) is a compound containing cobalt (Co), and examples of the coloring element source include tricobalt tetroxide (Co 3 O 4 ), cobalt(III) oxide (Co 2 O 3 ), cobalt(II) oxide (CoO), cobalt oxyhydroxide (CoOOH), cobalt hydroxide (Co(OH) 2 ), cobalt nitrate (Co(NO 3 ) 2 ), cobalt chloride (CoCl 2 ) and cobalt sulfate (CoSO 4 ) group, and Co 3 O 4 , Co 2 O 3 , CoO and CoOOH. is preferred.

[0088] When the coloring element is iron, the coloring element source (iron source) is a compound containing iron (Fe), for example, iron (III, II) oxide (Fe 3 O 4 ), iron(III) oxide (Fe 2 O 3 ), iron(II) oxide (FeO), iron oxyhydroxide (FeOOH), iron hydroxide (FeOH), iron nitrate (Fe(NO 3 ) 2 ), iron chloride (FeCl) and iron sulfate (FeSO4 ) group, and Fe 3 O 4 , Fe 2 O 3 , FeO and FeOOH.

[0089] When the coloring element is aluminum, the coloring element source (aluminum source) is a compound containing aluminum (Al), for example, alumina (Al 2 O 3 ), aluminum hydroxide (Al(OH) 3 ), aluminum chloride (AlCl 3 ), aluminum isopropoxide (C 9 H 21 O 3 Al and aluminum nitrate (Al(NO 3 ) 3 ) and preferably at least one of alumina and aluminum hydroxide.

[0090] When the coloring element is manganese, the coloring element source (manganese source) is a compound containing manganese (Mn), such as manganese oxide (MnO), manganese dioxide (MnO 2 ), Manganese tetraoxide (Mn 3 O 4 ), manganese hydroxide (Mn(OH) 2 ), manganese oxyhydroxide (MnOOH), manganese sulfate (MnSO 4 ), manganese nitrate (Mn(NO 3 ) 2 ) and manganese chloride (MnCl 2 ) may be mentioned, and at least one selected from the group consisting of manganese dioxide, manganese trioxide and manganese hydroxide is preferred.

[0091] When the coloring element is silicon, the coloring element source (silicon source) is a compound containing silicon (Si), and includes at least one selected from the group consisting of colloidal silica, precipitated silica, amorphous silica, sodium silicate, tetraethyl orthosilicate, and silica powder, and is preferably silica powder.

[0092] The content of the stabilizer in the transparent raw material is preferably an amount that stabilizes zirconia in a cubic fluorite structure by sintering. For example, when the stabilizer is yttria, the content of yttria is 6 mol% to 12 mol%, preferably 7 mol% to 12 mol%, more preferably 8 mol% to 11 mol%, and even more preferably 8 mol% to 10 mol%.

[0093] The content of titania in the transparent raw material is 3 mol % or more and 20 mol % or less, preferably 5 mol % or more and 15 mol % or less, and more preferably 8 mol % or more and 12 mol % or less.

[0094] The content of the stabilizer in the opaque raw material is preferably an amount that stabilizes zirconia in a tetragonal fluorite structure by sintering. For example, when the stabilizer is yttria, the content of yttria is 2 mol% to 6 mol%, preferably 2 mol% to 4 mol%, more preferably 2.5 mol% to 3.5 mol%.

[0095] The titania content of the opaque raw material is 1 mol % or more and 7 mol % or less, and preferably 1.5 mol % or more and 6 mol % or less.

[0096] The content of the coloring element source in the opaque raw material may be any content depending on the desired color tone, and may be, for example, 0.01% by mass to 50% by mass, preferably 0.1% by mass to 20% by mass, and more preferably 0.3% by mass to 10% by mass. For example, the coloring element source is, for example, 0.01% by mass to 50% by mass of cobalt relative to the mass of the opaque raw material. 3 O 4The converted mass is 0.1% by mass or more and 5% by mass or less, and the Fe content is 0.1% by mass or more and 5% by mass or less relative to the mass of the opaque raw material. 2 O 3 The mass of the opaque raw material is 0.1% by mass or more and 5% by mass or less, and the mass of nickel is 0.1% by mass or more and 10% by mass or less, and the mass of aluminum ... nickel is 0.1% by mass or more and 10% by mass or less, and the 2 O 3 The converted mass is 0.1 mass % or more and 40 mass % or less.

[0097] In order to improve the fluidity of the raw material powder, at least one of the transparent raw material and the opaque raw material may contain an organic binder. When the organic binder is contained, the content of the organic binder in each raw material powder can be, for example, 25% by volume or more and 65% by volume or less, and further 35% by volume or more and 60% by volume or less.

[0098] The organic binder may be a known one used in molding ceramic powder, for example, one containing at least one selected from the group consisting of acrylic resin, wax, and plasticizer. In this embodiment, the acrylic resin may be a polymer containing at least one of an acrylic acid ester residue unit or a methacrylic acid ester residue unit.

[0099] The transparent raw material and the opaque raw material are preferably in a state in which raw materials such as the zirconia source are uniformly mixed. The raw materials may be mixed by any method, and may be at least one of dry mixing and wet mixing, and wet mixing is preferable. A preferred wet mixing method is mixing by at least one of a ball mill and a stirring mill, and mixing by a ball mill using zirconia balls with a diameter of 1.0 mm to 10.0 mm is preferable. When a coloring element is contained, it is more preferable to mix the coloring element source and then mix the zirconia source and the coloring element source.

[0100] When the raw material powder contains an organic binder, any mixing method can be used as long as the raw material powder and the organic binder can be mixed uniformly. Examples of the mixing method include heat kneading and wet mixing.

[0101] In the case of obtaining a zirconia sintered body having an opaque zirconia portion made of a black zirconia sintered body, the opaque raw material (hereinafter also referred to as a "black raw material") is preferably a mixed powder containing a cobalt source, an iron source, and an alumina source, with the balance being yttria and titania-containing zirconia, and 3 O 4 Cobalt, Fe, equivalent to 0.02% or more by mass and 0.2% or less by mass 2 O 3 Iron and Al, calculated as 0.03% or more by mass and 0.5% or less by mass 2 O 3 It is preferable that the mixed powder contains 0.1 mass % or more and 30 mass % or less of aluminum converted into aluminum, and the balance is zirconia containing 2 mol % or more and 6 mol % or less of titania and 2 mol % or more and 4 mol % or less of yttria. The black raw material may contain at least one of a manganese source and a silica source, and may further contain a manganese source, as necessary.

[0102] The ratio of the cobalt source and the iron source in the black raw material is arbitrary, but the cobalt and iron in the black raw material are each Co 3 O 4 and Fe 2 O 3 The weight ratio when converted as Co 3 O 4 / (Co 3 O 4 +Fe 2 O 3 ) is preferably 0.10 or more and 0.99 or less, and more preferably 0.10 or more and 0.50 or less.

[0103] In the black raw material, the cobalt source, the iron source and the aluminum source may be present in the form of a composite oxide containing two or more selected from the group consisting of cobalt, iron and aluminum. 2 O 4(Cobalt ferrite), CoAl 2 O 4 (Cobalt Aluminate), FeAl 2 O 4 and FeAlO 3 Examples of the compound include one or more selected from the group consisting of CoAl 2 O 4 is preferred.

[0104] The difference in linear shrinkage between the transparent raw material and the opaque raw material (hereinafter, simply referred to as "linear shrinkage difference") is preferably 5.0% or less. Usually, the thermal shrinkage behavior of the transparent raw material and the opaque raw material is significantly different from that of the transparent raw materials or the opaque raw materials, so that defects are likely to occur when sintered together, and the yield is likely to be significantly reduced. In contrast, in this embodiment, the linear shrinkage difference is 5.5% or less, or even 5.0% or less, so that defects are unlikely to occur when sintered, and the yield is likely to be high. The linear shrinkage difference is any one of 4.5% or less, 4.0% or less, 3.5% or less, 3.0% or less, 2.5% or less, and 2.0% or less. Since the linear shrinkage of raw material powders with different compositions is difficult to match, the linear shrinkage difference is 0% or more, or even 0.1% or more.

[0105] The "linear shrinkage rate" in this embodiment is one of the indexes of thermal shrinkage behavior, and can be calculated by subjecting a rectangular parallelepiped sample (e.g., a rectangular parallelepiped sample having a width of 30 mm, a thickness of 3 mm, and a length of 40 mm) (hereinafter also referred to as a "rectangular parallelepiped sample") or a disk-shaped sample (e.g., a disk-shaped sample having a diameter of 22 mm and a thickness of 1 mm) (hereinafter also referred to as a "disk sample") to a firing treatment as a measurement specimen, using the following formula from the values ​​before and after the firing treatment.

[0106] <Cuboid sample> S 1 =(S W +S T +S L ) / 3 Where: S w =100×{(L w2 -L w1 ) / L w1} S T =100×{(L T2 -L T1 ) / L T1} S L =100×{(L L2 -L L1 ) / L L1} It is. Also, S 1 is the linear shrinkage rate (%) of the rectangular sample, S W is the linear shrinkage rate of width (%), L w1 is the width of the rectangular sample before firing (mm), L w2 is the width of the rectangular sample after firing (mm), and S T is the linear shrinkage rate of thickness (%), L T1 is the thickness of the rectangular sample before firing (mm), L T2 is the thickness of the rectangular sample after firing (mm), and S L is the linear shrinkage rate (%), L L1 is the length of the rectangular sample before firing (mm), L L2 is the length (mm) of the rectangular parallelepiped sample after firing. The width, thickness and length can be measured using a vernier caliper.

[0107] <Disc sample> S 2 =(S D +S H ) / 2 Where: S D =100×{(L D2 -L D1 ) / L D1} S H =100×{(L H2 -L H1 ) / L H1} It is. Also, S 2 is the linear shrinkage rate (%) of the disk sample, S D is the linear shrinkage of the diameter (%), L D1 is the diameter of the disk sample before firing (mm), L D2 is the diameter of the disk sample after sintering (mm), and SH is the linear shrinkage rate of thickness (%), L H1 is the thickness of the disk sample before firing (mm), L H2 is the thickness (mm) of the disk sample after firing. The diameter and thickness can be measured using a vernier caliper. The diameter can be measured at two or three points and the average value can be used.

[0108] The firing treatment in the measurement of the linear shrinkage rate of this embodiment may be firing in air using a firing program with a heating rate of 100°C / h, a holding temperature of either 1300°C, 1400°C or 1500°C, a holding time of 1 minute and a heating rate of 200°C / h.

[0109] In this embodiment, the linear shrinkage difference (hereinafter, "ΔS (1300) "), and the linear shrinkage difference during firing at a holding temperature of 1400°C (hereinafter referred to as "△S (1400) "), or the linear shrinkage difference during firing at a holding temperature of 1500°C (hereinafter referred to as "ΔS (1500) It is preferable that one of the above linear shrinkage ratio differences is satisfied, but at least ΔS (1300) , △S (1400) and △S (1500) The maximum value of (hereinafter, "△S (MAX) It is more preferable that ΔS satisfies the above-mentioned value, and at least ΔS (1400) It is more preferable that satisfies the above-mentioned value.

[0110] Favorable △S (1300) is 0% or more, preferably 0.1% or more, and 5.0% or less, preferably 4.5% or less, more preferably 3.5% or less, even more preferably 3.0% or less, even more preferably 2.0% or less, and even more preferably 1.0% or less. (1400) is 0% or more, preferably 0.5% or more, and 5.0% or less, preferably 4.5% or less, more preferably 4.0% or less, and further preferably 3.5% or less. Furthermore, a preferable ΔS (1500)is 0% or more, preferably 0.1% or more, and 3.0% or less, preferably 2.0% or less, more preferably 1.8% or less, even more preferably 1.5% or less, and even more preferably 1.0% or less. (1300) and △S (1500) and the difference is more preferably 0% or more and 4.0% or less, further preferably 0% or more and 3.0% or less, further preferably 0% or more and 2.5% or less, further preferably 0% or more and 1.5% or less, further preferably 0% or more and 1.0% or less, and further preferably 0.1% or more and 0.5% or less.

[0111] In the sintering step, the secondary molded body is sintered to obtain a zirconia sintered body in which a transparent zirconia portion and an opaque zirconia portion are bonded together.

[0112] The sintering temperature for sintering the secondary molded body is preferably more than 1100° C., more preferably 1200° C. or higher, and even more preferably 1250° C. or higher. The sintering temperature may be any temperature that can be applied in a general sintering device, and may be 1700° C. or lower, or even 1600° C. or lower.

[0113] Any sintering method can be applied to the sintering step, and examples thereof include one or more methods selected from the group consisting of atmospheric sintering, microwave firing, and hot isostatic pressing (hereinafter also referred to as "HIP treatment"). In order to suppress the occurrence of defects at the interface between the transparent zirconia part and the opaque zirconia part, the sintering in the sintering step preferably includes at least HIP treatment, and more preferably atmospheric sintering and HIP treatment. In this embodiment, "atmospheric sintering" refers to a method of sintering without applying external pressure to the sintered object during firing. An atmospheric sintered body can be obtained by atmospheric sintering.

[0114] A preferred sintering method is to perform atmospheric sintering at 1300° C. to 1400° C., followed by HIP treatment at 1450° C. to 1550° C. In this way, the zirconia sintered body of the present embodiment can be made into a HIP-treated body.

[0115] The conditions for atmospheric sintering other than the sintering temperature are arbitrary, but the sintering atmosphere is either an oxidizing atmosphere or an air atmosphere, preferably an air atmosphere, and the sintering time is 30 minutes to 5 hours, preferably 1 hour to 3 hours.

[0116] The conditions of the HIP treatment other than the HIP treatment temperature are arbitrary, but examples thereof include using an inert gas, preferably at least one of nitrogen and argon, as a pressure medium, the HIP pressure being 50 MPa to 200 MPa, and the HIP treatment time being 0.5 hours to 10 hours. The HIP treatment atmosphere is preferably other than an oxidizing atmosphere, more preferably at least one of a reducing atmosphere and an inert atmosphere, and even more preferably a reducing atmosphere.

[0117] In the HIP treatment, it is preferable to place the sample under a reducing atmosphere during HIP sintering, and it is preferable to place the sample in a container made of a reducing material. Usually, reducing materials such as carbon are used for the components such as the heating element of the HIP treatment device. Therefore, even if an inert gas is used as a pressure medium, the atmosphere during HIP treatment is likely to be an unstable atmosphere ranging from an inert atmosphere to a weakly reducing atmosphere. However, by placing the sample under a reducing atmosphere during HIP sintering, it becomes easier to obtain the zirconia sintered body of this embodiment stably. Although the method of controlling the atmosphere during HIP treatment, particularly the atmosphere near the sample during HIP treatment, is arbitrary, it is convenient to place the sample in a container made of a reducing material. The atmosphere near the sample can be stabilized by selecting the material of the container in which the sample is placed during HIP treatment. For example, by placing the sample in a container made of oxide ceramics such as alumina, zirconia, or mullite, the sample can be placed under an inert atmosphere during HIP sintering. On the other hand, by placing the sample in a container made of a reducing material such as carbon, the sample can be placed under a reducing atmosphere during HIP treatment.

[0118] In the sintering step, it is preferable to perform an annealing treatment after sintering. This increases the linear transmittance of the transparent zirconia part. The annealing treatment can be performed under any conditions, but examples include an oxygen atmosphere (e.g., air atmosphere), a treatment temperature of 850°C to 950°C, and a treatment time of 0.5 to 2 hours.

[0119] The manufacturing method of this embodiment may include a processing step of processing the zirconia sintered body into an arbitrary shape. Processing can impart aesthetics more suited to the intended use, such as exposing the transparent zirconia part and the opaque zirconia part on the same surface, making the surface smoother, or finely modifying the shape.

[0120] Any processing method can be used, and examples thereof include one or more methods selected from the group consisting of lathe processing, surface grinding, R grinding, and NC (numerical control) processing. In order to enhance the gloss, examples of polishing methods include at least one of barrel polishing and R polishing. EXAMPLES

[0121] The zirconia sintered body of the present disclosure will be specifically described below with reference to examples and comparative examples. However, the present disclosure is not limited to the following examples. (Linear transmittance) A disk-shaped sintered body with a thickness of 1 mm and a diameter of 25 mm was prepared, and both surfaces were mirror-polished to a surface roughness of Ra = 0.02 μm or less to be used as a measurement sample. The linear transmittance was measured using a haze meter (device name: NDH5000, manufactured by Nippon Denshoku Co., Ltd.) with incident light of D65 light and a spot diameter of 15 mm.

[0122] (color tone) The color tone of the opaque zirconia part was measured by a method based on JIS Z 8722. A general color difference meter (device name: Spectrophotometer SD 3000, manufactured by Nippon Denshoku Industries Co., Ltd.) was used for the measurement, and the sample was placed against a white plate as the background (white back measurement). The measurement conditions were as follows: Light source: D65 light source Viewing angle: 10° Measurement method: SCE method (specular reflected light is removed and diffuse reflected light is measured) The color tone was measured by using a zirconia sintered body with a surface roughness of Ra=0.02 μm or less as a measurement sample, and measuring the color tone of the opaque zirconia part confirmed visually.

[0123] (Measurement of Linear Shrinkage Difference) The powder sample was molded under a pressure of 25 MPa by die press molding, and then subjected to CIP treatment under a pressure of 200 MPa to obtain a rectangular solid body with a width of 30 mm, a thickness of 3 mm, and a length of 40 mm, or a disk-shaped body with a diameter of 22 mm and a thickness of 1 mm, which were used as the measurement sample. W1 ), thickness (L T1 ) and length (L L1 ) for disk-shaped samples, and the diameter of the sample (L D1 ) and thickness (L H1 After the measurements, the compacts were sintered in air using a general sintering furnace (apparatus name: SC-2025H, manufactured by Motoyama Corporation) with a sintering program that set a heating rate of 100°C / h, a holding temperature of either 1300°C, 1400°C or 1500°C, a holding time of 1 minute, and a temperature drop rate of 200°C / h. For the measurement samples after sintering using the sintering program set for each holding temperature, the width (L W2 ), thickness (L T2 ) and length (L L2 ) for disk-shaped samples, and the diameter of the sample (L D2 ) and thickness (L H2 The linear shrinkage rates were calculated from the obtained values, and the average value was calculated as the linear shrinkage rate (S 1 ,S 2 The difference in linear shrinkage between the samples was taken as the linear shrinkage difference.

[0124] (Biaxial bending strength) A disk-shaped sintered body with a thickness of 1 mm and a diameter of 25 mm (or 12 mm) was prepared, and both surfaces were mirror-polished to a surface roughness (Ra) of 0.02 μm or less, which was used as a measurement sample. The measurement sample was used to measure biaxial bending strength in accordance with the biaxial bending strength measurement specified in ISO / DIS6872. In the biaxial bending strength measurement, three supports were placed according to the shape of the measurement sample so that the interface between the transparent zirconia part and the opaque zirconia part was located inside the support circle, and the diameter of the support circle was 22 mm or 11 mm. Zirconia balls with a ball diameter of 9.5 mm were used as supports, and a load was applied so that the load was applied to the transparent zirconia part.

[0125] (EPMA measurement) Using an EPMA device (device name: EPMA1610, manufactured by Shimadzu Corporation), observation of the backscattered electron image and element mapping were performed under the following conditions. Measurement method: wavelength dispersion type Accelerating voltage: 15kV Irradiation current: 300nA Analysis area: 51.2μm×51.2μm Number of fields of view: 3 Using the analysis software attached to the EPMA1610 (product name: EPMA System Ver.2.14, manufactured by Shimadzu Corporation), the obtained elemental mapping was binarized and the number of areas where the intensity of the characteristic X-rays of cobalt or iron in the background was 1.5 times or more was counted. The Co distribution, Fe distribution, modal Co distribution, and modal Fe distribution were obtained from the ratio of the number of each area to the number of areas counted. The sintered body samples used were disk-shaped sintered bodies with a surface roughness of Ra = 0.02 μm or less, a thickness of 1 mm, and a diameter of 16 mm.

[0126] Example 1 (transparent raw material) BET specific surface area is 5.3m 2 / g, and a zirconia powder containing 10 mol% yttria and a BET specific surface area of ​​20 m 2Titania powder having a molecular weight of 1000 to 10000g / g was mixed in an ethanol solvent using a ball mill made of zirconia balls having a diameter of 10 mm. The ball mill mixing was performed by crushing the titania powder in an ethanol solvent and further mixing it with yttria-containing zirconia powder. The mixed powder was dried in the air to obtain a zirconia powder containing 10 mol % yttria and 9.1 mol % titania, which was used as the transparent raw material. Titanium (Ti) in the titania contained in the transparent raw material was calculated as the ratio of TiO 2 This corresponds to a titanium mass percentage of 6.8 mass%.

[0127] (opaque raw material) Alumina powder, iron oxide powder, cobalt oxide powder, zirconia powder containing 3 mol% yttria, and titania powder were wet mixed in an ethanol solvent using a ball mill using zirconia balls to obtain a mixed powder containing 0.25 mass% alumina, 0.16 mass% iron oxide, 0.04 mass% cobalt oxide, and the remainder being 3 mol% yttria and 4.7 mol% titania-containing zirconia. The mixed powder was dried at 110°C in air and then sieved to obtain an opaque raw material (black raw material). Titanium (Ti) in titania contained in the opaque raw material was calculated as the ratio of TiO 2 This corresponds to a converted titanium mass percentage (hereinafter also referred to as "titanium mass percentage") of 3.0 mass%.

[0128] (Molded body) A transparent raw material was filled into a circular plate-shaped primary mold having a diameter of 25 mm and an uneven shape, and a primary molded body consisting of a circular plate-shaped transparent molded body having a thickness of 2 mm and a diameter of 25 mm was obtained by uniaxially pressing the primary molded body with a diameter of 50 mm so that the convex shape of the primary molded body was the upper surface. An opaque raw material was filled so that the entire upper surface of the primary molded body was covered. Then, the primary molded body was uniaxially pressed at a pressure of 50 MPa to obtain a secondary molded body in which a transparent molded body and an opaque molded body were laminated, and the secondary molded body was subjected to CIP treatment at a pressure of 200 MPa. As a result, a circular plate-shaped secondary molded body having a thickness of 3.5 mm and a diameter of 50 mm was obtained. FIG. 2 is a schematic diagram showing a cross section of a secondary molded body (200), and shows a secondary molded body in which a transparent molded body and an opaque molded body are laminated, in which a primary molded body (201) consisting of a transparent molded body is placed in a secondary molded body (210) and the exposed surface of the primary molded body is covered with an opaque molded body (202).

[0129] (Zirconia sintered body) The resulting secondary compact was sintered under atmospheric pressure in air at a heating rate of 100°C / h, a sintering temperature of 1350°C, and a sintering time of 2 hours, and then HIP-treated at a temperature of 1500°C, a pressure of 150MPa, and a holding time of 1 hour. After HIP-treatment, the sample was annealed in air at 900°C for 8 hours to obtain a sintered body. In the HIP-treatment, argon gas with a purity of 99.9% was used as the pressure medium, and the sample was placed in a carbon container with a lid.

[0130] The annealed sintered body was cut and polished until a transparent zirconia portion and an opaque zirconia portion were exposed on both sides of the sintered body, resulting in a disk-shaped zirconia sintered body having a thickness of 1.0 mm and including a transparent zirconia portion and an opaque zirconia portion, the transparent zirconia portion and the opaque zirconia portion being exposed on the same surface, which was used as the zirconia sintered body of this example.

[0131] FIG. 3 is a schematic diagram showing the appearance of the front (300a) and cross section (300b) of the zirconia sintered body of this embodiment after cutting and polishing. As shown in the front view (300a), the zirconia sintered body of this embodiment has a structure in which the opaque zirconia part (302) is arranged to surround the transparent zirconia part (301), and the transparent zirconia part (301) and the opaque zirconia part (302) have a disk shape exposed on the same surface. Also, as shown in the cross section (300b), the zirconia sintered body of this embodiment has a transparent zirconia part that is continuous in the thickness direction. Due to the transparency of the transparent zirconia part, when the zirconia sintered body of this embodiment is arranged, it functions like a window material, and the design of the background can be visually recognized.

[0132] The annealed zirconia sintered body was subjected to composition analysis by EPMA. The EPMA composition analysis confirmed that the transparent zirconia part of the zirconia sintered body did not contain cobalt (below the detection limit) in the region 10 μm from the interface.

[0133] In this embodiment, the linear shrinkage difference is ΔS (1300) is 0.8%, △S (1400) is 3.0% and △S (1500) is 0.6%, and △S (MAX) is 3.0%, and △S (1300) and △S (1500) The difference was found to be 0.2%.

[0134] Examples 2 and 3 The mixing ratio of alumina powder, iron oxide powder, cobalt oxide powder, zirconia powder containing 3 mol% yttria (or zirconia powder containing 4 mol% yttria) and titania powder was changed to obtain an opaque raw material (black raw material) so as to have the following composition, a primary molded body consisting of a disk-shaped transparent molded body having a thickness of 5 mm and a diameter of 12 mm was produced using a disk-shaped primary mold having a diameter of 12 mm and an uneven shape, and a disk-shaped secondary molded body having a thickness of 4 mm and a diameter of 25 mm was obtained in the same manner as in Example 1, except that the zirconia sintered body of each Example was obtained in the same manner as in Example 1. In each Example, the titanium mass ratio was 3.0 mass%.

[0135] [Table 1]

[0136] Examples 4 to 11 (Transparent raw material, opaque raw material) Zirconia powder containing 10 mol % yttria and 9.1 mol % titania obtained in the same manner as in Example 1 was used as a transparent raw material.

[0137] Further, a mixed powder was obtained in the same manner as in Example 1, except that the mixing ratio of the alumina powder, iron oxide powder, cobalt oxide powder, zirconia powder containing 3 mol% yttria, and titania powder was changed to obtain the following composition, and this was used as an opaque raw material (black raw material). The composition of the obtained opaque raw material is shown in the table below. The titanium mass ratio is 4.0 mass% in Examples 4 to 8, and 5.0 mass% in Examples 9 to 11.

[0138] [Table 2]

[0139] (Sintered body) A disk-shaped secondary body having a thickness of 4 mm and a diameter of 23 mm was obtained in the same manner as in Example 1, except that each opaque raw material was used, a disk-shaped primary mold having a diameter of 12 mm and an uneven shape was used to produce a primary molded body consisting of a disk-shaped transparent molded body having a thickness of 5 mm and a diameter of 12 mm, and the primary molded body was used. The obtained secondary molded body was treated in the same manner as in Example 1 to obtain a zirconia sintered body of each Example.

[0140] The obtained zirconia sintered bodies were all 1.0 mm thick, and had a transparent zirconia part and an opaque zirconia part, and were disk-shaped zirconia sintered bodies in which the transparent zirconia part and the opaque zirconia part were exposed on the same surface. When the color tone of the opaque zirconia part of Examples 2, 4 and 5 was measured, the lightness L * is 0.74, hue a * is 0.05 and hue b * is -0.20 (Example 4), and lightness L * 2.64, hue a * is 0.65 and hue b * 0.78 (Example 6), lightness L * 6.75, hue a * is 1.33 and hue b * was 2.66 (Example 7).

[0141] Examples 12 to 15 The zirconia sintered bodies of each Example were obtained in the same manner as in Example 2, except that an opaque raw material (black raw material) was obtained by changing the mixing ratio of iron oxide powder, cobalt oxide powder, zirconia powder containing 3 mol% yttria, and titania powder so as to have the following composition. The titanium mass ratio was 3.0 mass% in each Example.

[0142] [Table 3]

[0143] Examples 16 to 23 The zirconia sintered bodies of each Example were obtained in the same manner as in Example 2, except that an opaque raw material (black raw material) was obtained by changing the mixing ratio of alumina powder, iron oxide powder, cobalt oxide powder, zirconia powder containing 3 mol% yttria (or zirconia powder containing 4 mol% yttria), titania powder, and manganese tetraoxide powder so as to have the following composition. The titanium mass ratio was 3.0 mass% in Example 16, and 4.0 mass% in Examples 17 to 23.

[0144] [Table 4]

[0145] In addition, the linear shrinkage difference was measured for Examples 17 to 19. The linear shrinkage difference for Example 17 was ΔS (1300) 4.1%, △S (1400) is 5.2% and △S (1500) is 1.9%, and Example 18 is △S (1300) 4.9%, △S (1400) is 4.8% and △S (1500) is 1.9%, and Example 19 is △S (1300) 5.9%, △S (1400) is 5.0% and △S (1500) was 1.9%.

[0146] Comparative Example 1 According to JP2013-14471A, a ceramic bonded body was obtained as follows.

[0147] (Black zirconia sintered body) Black zirconia powder (product name: TZ-Black, manufactured by Tosoh Corporation) was uniaxially pressurized at a pressure of 50 MPa, and then subjected to CIP treatment at a pressure of 200 MPa to obtain a plate-shaped molded body of 30 mm in length and 40 mm in width. The obtained molded body was sintered under normal pressure, and then the obtained zirconia sintered body was machined to obtain a frame-shaped black zirconia sintered body of 1.15 mm in thickness, 28 mm in length, and 36 mm in width, with a rectangular hollow part of 1.15 mm in thickness, 14 mm in length, and 22 mm in width.

[0148] (Transparent zirconia sintered body) High-purity titania powder was added to 10 mol% yttria-containing zirconia powder (product name: TZ-10YS, Tosoh Corporation) at 10 mol% relative to the zirconia, and mixed in an ethanol solvent with a zirconia ball of 10 mm diameter for 72 hours, then dried to obtain raw material powder. The raw material powder was uniaxially pressed at a pressure of 50 MPa, and then CP-treated at a pressure of 200 MPa to obtain a plate-shaped molded body of 2 mm thickness, 50 mm length, and 40 mm width.

[0149] The obtained plate-shaped compact was sintered under atmospheric pressure in air at a heating rate of 100°C / h, a sintering temperature of 1350°C, and a sintering time of 2 hours to obtain an atmospheric sintered compact. Next, this atmospheric sintered compact was HIP-treated at a temperature of 1650°C, a pressure of 150MPa, and a holding time of 1 hour. The HIP treatment used argon gas with a purity of 99.9% as the pressure medium, and the sample was placed in a carbon container with a lid. After HIP-sintering, the sample was annealed in air at 1000°C for 1 hour to obtain a transparent zirconia sintered compact.

[0150] (Ceramics Bonding Body) A ceramic bonded body was obtained by placing a transparent zirconia sintered body inside the black zirconia sintered body and performing HIP treatment at a pressure of 150 MPa, a holding temperature of 1200°C, and a holding time of 1 hour. The HIP treatment was performed at a holding temperature of 1200°C, a pressure of 150 MPa, and a holding time of 1 hour, using argon (Ar) gas with a purity of 99.9% as the pressure medium, and the sample was placed in an alumina container. After the HIP treatment, the HIP sintered body obtained at 1000°C for 1 hour in air was annealed to obtain the zirconia bonded body of this comparative example.

[0151] The results of the biaxial bending strength measurements of these Examples and Comparative Examples are shown in the table below.

[0152] [Table 5]

[0153] The zirconia sintered bodies of the Examples all had a biaxial bending strength of 350 MPa or more, further a biaxial bending strength of more than 400 MPa, and further a biaxial bending strength of 600 MPa or more, whereas the zirconia joined body of Comparative Example 1 had a biaxial bending strength of less than 250 MPa. In addition, when the source of fracture of the zirconia joined body of Comparative Example 1 was confirmed, it was confirmed that the fracture occurred from the portion where the black zirconia sintered body and the translucent zirconia sintered body came into contact (the joining surface).

[0154] Synthesis Example 1 (Transparent Zirconia Sintered Body) A primary molded body was obtained in the same manner as in Example 1. A transparent zirconia sintered body was produced in the same manner as in Example 1, except that the obtained primary molded body was used instead of the secondary molded body.

[0155] The obtained zirconia sintered body exhibited transparency similar to that of the transparent zirconia portion of the zirconia sintered body of Example 1, with an in-line transmittance of 69% and an average crystal grain size of 25 μm.

[0156] The biaxial bending strength of the transparent zirconia sintered body was 181 MPa, which was a lower value than the biaxial bending strength of the zirconia sintered body of the Example.

[0157] Synthesis Example 2 (Black zirconia sintered body) A primary molded body was obtained in the same manner as in Example 1, except that the raw material powder for the opaque zirconia part was used instead of the raw material powder for the transparent zirconia part. A black zirconia sintered body was produced in the same manner as in Example 1, except that the obtained primary molded body was used instead of the secondary molded body.

[0158] The obtained zirconia sintered body had a color tone similar to that of the opaque zirconia part of the zirconia sintered body of Example 1, a linear transmittance of 0% (below the detection limit), an average crystal grain size of 1.1 μm, and a monoclinic phase rate of 0%.

[0159] Examples 24 to 26 The zirconia sintered bodies of each Example were obtained in the same manner as in Example 2, except that opaque raw materials (black raw materials) were obtained by changing the mixing ratio of alumina powder, iron oxide powder, cobalt oxide powder, 4 mol% yttria-containing zirconia powder, titania powder, and silica powder so as to have the following composition. The titanium mass ratio was 4.0 mass% in each Example.

[0160] [Table 6]

[0161] Example 27 (transparent raw material) A zirconia powder containing 10 mol % yttria and 9.1 mol % titania was obtained in the same manner as in Example 1. The titanium (Ti) in the titania contained in the mixed powder was calculated as the ratio of TiO 2 This corresponds to 6.8% by mass as the mass ratio of titanium. The powder was mixed with an organic binder containing an acrylic resin to form a composition, which was used as the transparent raw material of this example.

[0162] (opaque raw material) A mixed powder containing 0.25 mass% alumina, 0.16 mass% iron oxide, 0.04 mass% cobalt oxide, and the remainder being 3 mol% yttria and 4.7 mol% titania-containing zirconia was obtained in the same manner as in Example 1. The titanium (Ti) in the titania contained in the mixed powder was calculated as the ratio of TiO 2 This corresponds to 3.0% by mass as the mass ratio of titanium. The mixed powder was mixed with an organic binder containing an acrylic resin to prepare a composition, which was used as the opaque raw material of this example.

[0163] (Molded body) A transparent raw material was injection molded into a primary mold to obtain a primary molded body consisting of a disc-shaped transparent molded body having an uneven shape and a thickness of 2 mm and a diameter of 25 mm. The obtained primary molded body was placed in a disc-shaped secondary mold having a diameter of 50 mm so that the uneven shape of the primary molded body was on the upper surface. An opaque raw material was injection molded onto the primary molded body so that the entire upper surface (exposed surface) of the primary molded body was covered, and a secondary molded body having a thickness of 3.5 mm and a diameter of 50 mm, in which a transparent molded body and an opaque molded body were laminated, was obtained.

[0164] (Zirconia sintered body) Except for using the obtained secondary molded body, normal pressure sintering, HIP treatment, annealing treatment and processing were performed in the same manner as in Example 1, thereby obtaining a zirconia sintered body of this example.

[0165] The zirconia sintered body of this example was a disk-shaped sintered body having a thickness of 1 mm, and a transparent zirconia portion and an opaque zirconia portion were exposed on the same surface. [Explanation of symbols]

[0166] 100a, 100b, 200a, 200b: Zirconia sintered body 101, 301: Transparent zirconia part 102, 302: Opaque zirconia part 110a, 110b, 110c: Support 120: Load 200: Secondary molded body 201: Primary molding (transparent molding) 202: Opaque molded body 210: Secondary mold

Claims

1. A zirconia sintered body having a shape including a structure in which either the transparent zirconia part or the opaque zirconia part is arranged to surround the other, the zirconia sintered body being characterized in that the biaxial bending strength measured in accordance with the biaxial bending strength measurement specified in ISO / DIS6872 is 300 MPa or more when a load having a size smaller than the interface is applied to the center of gravity of the fulcrum diameter of the zirconia sintered body arranged so that an interface surrounding the transparent zirconia part or the opaque zirconia part fits within a circle drawn by connecting fulcrums for placing the zirconia sintered body and the interface fits within the circle.

2. 2. The zirconia sintered body according to claim 1, wherein the transparent zirconia portion and the opaque zirconia portion are on the same plane.

3. The zirconia sintered body according to claim 1 or 2, wherein the transparent zirconia portion has an in-line transmittance of 50% or more.

4. The zirconia sintered body according to any one of claims 1 to 3, wherein the in-line transmittance of the opaque zirconia portion is less than 5%.

5. The zirconia sintered body according to any one of claims 1 to 4, wherein the transparent zirconia portion and the opaque zirconia portion contain zirconia containing a stabilizer and titania.

6. The zirconia sintered body according to claim 5, wherein the stabilizer is at least one selected from the group consisting of yttria, calcia and magnesia.

7. The zirconia sintered body according to claim 5 or 6, wherein the stabilizer for the transparent zirconia portion is yttria, and the yttria content is 6 mol% or more and 12 mol% or less.

8. The zirconia sintered body according to any one of claims 5 to 7, wherein the stabilizer for the opaque zirconia portion is yttria, and the yttria content is 2 mol% or more and less than 6 mol%.

9. The zirconia sintered body according to any one of claims 5 to 8, wherein the opaque zirconia portion has a lower titania content than the transparent zirconia portion.

10. The zirconia sintered body according to any one of claims 1 to 9, wherein the opaque zirconia portion contains a coloring element.

11. The zirconia sintered body according to claim 10, wherein the coloring element is at least one selected from the group consisting of transition metal elements, alkali metal elements, alkaline earth metal elements, aluminum, silicon, boron, phosphorus, germanium, and rare earth elements.

12. The zirconia sintered body according to any one of claims 1 to 11, characterized in that the biaxial bending strength is 350 MPa or more.

13. 13. The method for producing a zirconia sintered body according to any one of claims 1 to 12, further comprising a sintering step of sintering a primary molded body made of either a raw material powder of a transparent zirconia part or a raw material powder of an opaque zirconia part and having at least one of a convex shape and a concave shape, and a secondary molded body having a structure in which a molded body made of the other raw material powder is laminated so as to cover the outer structure.

14. The method for producing a zirconia sintered body according to claim 13, wherein the raw material powder for the transparent zirconia part and the raw material powder for the opaque zirconia part are mixed powders containing a stabilizer-containing zirconia source and a titania source, respectively.

15. The method for producing a zirconia sintered body according to claim 13 or 14, wherein the sintering includes at least a HIP treatment.

16. 16. The method according to claim 13, further comprising the steps of: sintering at atmospheric pressure at 1,300° C. to 1,400° C.; and then performing HIP treatment at 1,450° C. to 1,550° C.

Citation Information

Patent Citations

  • Method for joining ceramic member

    JP1994191959A

  • Method for manufacturing joined sintered compact and joined sintered compact

    JP2007254225A

  • Method for producing ceramic sintered compact

    JP2011093779A

  • Translucent ceramic joint, and method for manufacturing the same

    JP2013014472A

  • Method for manufacturing shower plate, shower plate and plasma processing apparatus

    JP2013179062A